Um ato de fé e(m) festa análise do encontro entre devoção e diversão na dança de São Gonçalo de Amarante - Oliveira, Victor Hugo Neves de (2011)
The purpose of the research proposal is to observe and examine certain relationships established between body, dance and religion in the ritual practice of São Gonçalo de Amarante held in Mussuca/ Laranjeiras (SE) from the meeting between devotion and entertainment phenomena which reveal points of relatedness between artistic representations and expressions of popular piety, helping us to seize the planes of intersections and dialogues between categories of the sacred and the profane in a ceremonial context. Initially, the study aims to investigate the general framework of images, legends and stories that motivate the ritual, examining the interaction of mythic substance through developing and sharing the ontological sacred in the process of fixing and reorganization of Dança de São Gonçalo de Amarante. The second stage is to analyse the construction of the space by seizing it as a value system that cooperates in the development of observation and interpretation of situations of ritual and finally, to discuss intersections between devotion and entertainment in the action and meanings produced by the body in motion within the cult, providing scope for meaningful discourse about the act of faith and the piety